Comparison of Dengue Hemorrhagic Fever (DHF) Cases Between Male and Female in Bandung City - Nisrina Deyan Maharani; Indri Wijaya; Gilang Germana; Aqilah Febrianti Zhafira; Ayesha Ghania Hafiza; Lovely Tiara; Ali Fatih M; Safa Nur Azkia; Nur Rusyda Fathia; Putri Nabilah Sehan; Rahma Oka Subekti; Rahmat Hibatul Hadi; Yuyun Hidayat (Research Collaboration Community (RCC), 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that is a serious health problem in tropical regions such as Indonesia, including Bandung City, which has a high population density and environmental conditions that support the development of the Aedes aegypti vector. This study aims to determine the difference in the number of DHF cases between men and women in Bandung City during the period 2023-2024. Secondary data were obtained from two different sources and analyzed using the chi-squared statistical test. The combined results show that the number of DHF cases in men was 1,607 cases, which shows a higher number compared to women, who had 1,590 cases. The calculated value in 2023 was 0.65, and in 2024, it was 0.015. While the combined data in 2023-2024 had a X2 Value of 0.5708. This shows that the results of the three calculations are smaller than the X2 Table value of 3.84 (α = 0.05; df = 1), so the null hypothesis is accepted and the alternative hypothesis is rejected. Thus, it can be concluded that there is no significant difference in the number of dengue fever cases between men and women. This finding suggests that gender is not a determining factor in the spread of dengue fever cases in Bandung City.